Výskyt Echinococcus multilocularis Leuckart, 1863 u lisek (Vulpes vulpes) v Ceské republice - Pavlásek, I; Chalupský, J; Kolárová, L; Horyna, B; Ritter, J (Epidemiologie, mikrobiologie, imunologie, 1997)
During the period between December 1994 and December 1996 the authors examined, using the method of helminthological dissection of the intestinal tract in 15 districts of four regions in the Czech Republic a total of 824 foxes from 350 land registers. Echinococcus multilocularis was found in the following regions: South Bohemian (districts Jindrichův Hradec, Ceský Krumlov, Prachatice and Strakonice), Central Bohemian (Benesov district) and North Bohemian (district Teplice and Chomutov). There were 87 positive (10.6%) foxes in 56 places (16%). In some areas of the South Bohemian region examinations of foxes were repeated. It was found that there are places where the prevalence of E. multilocularis varied between 28.6 and 75% (mean 53.7%) but also areas which were repeatedly negative. In 1996 after one-week intervals foxes from the Prachatice district (South Bohemian region) were sent for parasitological examination. During different months of the year the prevalence of E. multilocularis varied between 2.6 and 33.3%. A similar investigation was made during May to October 1996 (except September) also in the district of Ceský Krumlov (South Bohemian region). Tapeworms were found in 7.14 to 66.7% of foxes.
Keywords: Česká republika; Foxes; zvířata; Echinococcus; Czech Republic; lišky; Animals